2013
DOI: 10.1590/s2175-78602013000200005
|View full text |Cite
|
Sign up to set email alerts
|

A importância da luz na ocupação de árvores por lianas

Abstract: ResumoLianas interagem de forma negativa com as árvores, uma vez que aumentam suas taxas de mortalidade. Seria esperado, portanto, que árvores apresentassem possíveis caracteres que as defenderiam contra lianas. O objetivo desse estudo foi testar se os seguintes caracteres das árvores limitam sua infestação por lianas: 1) baixa altura; 2) tronco com ramificações altas (fuste alto); 3) casca lisa; 4) casca esfoliante, e 5) menor índice de iluminação da copa. O estudo foi realizado em um fragmento de Floresta Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…First, as one liana reaches the forest canopy, other liana can climb it. As the local features of rooting point of lianas can be important for their probability of interaction with trees in the neighbourhood (Nesheim & Økland 2007;Nogueira et al 2011), trees with more exposed canopies generally have more lianas (Sfair et al 2013(Sfair et al , 2016 and taller trees can contribute more to nestedness probably because lianas climb preferentially on them. Second, it is reasonable to consider that taller trees are generally older and have had more time to accumulate lianas (P erez-Salicrup et al 2001;Malizia & Grau 2006;Campanello et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, as one liana reaches the forest canopy, other liana can climb it. As the local features of rooting point of lianas can be important for their probability of interaction with trees in the neighbourhood (Nesheim & Økland 2007;Nogueira et al 2011), trees with more exposed canopies generally have more lianas (Sfair et al 2013(Sfair et al , 2016 and taller trees can contribute more to nestedness probably because lianas climb preferentially on them. Second, it is reasonable to consider that taller trees are generally older and have had more time to accumulate lianas (P erez-Salicrup et al 2001;Malizia & Grau 2006;Campanello et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Lianas and trees interact antagonistically (Stewart & Schnitzer 2017) and compete mainly for nutrients and light (Dillenburg et al 1993;Schnitzer et al 2005;Cai et al 2009;Alvarez-Cansino et al 2015). In fact, lianas are very opportunistic and tend to climb closer (Roeder et al 2015) and taller trees (Sfair et al 2013(Sfair et al , 2016, and consequently, liana traits can play a minor role on tree species preference. In spite of these negative effects, our results showed that the lianas traits are less important in predicting their occupation on a tree species than their abundance and, consequently, their contribution to nestedness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations